(3GdTYhQ HGdYhQs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GJUa HGdceGd hHYO aEf GdJUfja af dGjedg ef GYJGOg s
(3BNQgG (B:s
(3GdfgGjI (B: (3JQLeI jhSa Hf eMeO Hf YHjO Gddg GdbGVi hBNQ eG ajg hcGf jcJH NWkG QOjkG VYjakG hde jRd Ydi MGdg Edi Cf Jhai QMeg Gddg Je cJGH GdTYhQ HGdYhQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs